Search for the Charmed Baryonium and Dibaryon Structures via the QCD Sum Rules - Wang, Xiu-Wu; Wang, Zhi-Gang (Advances in High Energy Physics, 2022)
In the present work, we construct eight six-quark currents to study the ΣcΣ¯c baryonium and ΣcΣc dibaryon states via the QCD sum rules. For either ΣcΣ¯c baryonium or ΣcΣc dibaryon states, we construct four currents with the JP=1−,1+,0+ and 0−. Except the current 1+ of ΣcΣc, we find the Borel windows for the other seven. There are two possible ΣcΣ¯c molecular states or compact six-quark states with the JP=1− and 0−. The results of the current 0+ of ΣcΣc show a possible ΣcΣc molecular state with 20 MeV binding energy. We find two ΣcΣ¯c baryonium resonances states with the JP=1+,0+ and two ΣcΣc dibaryon resonances states with the JP=0−,1−, respectively. Pole residues of the seven states are also calculated.